2016
DOI: 10.17795/ijpbs-3868
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Body Dysmorphic Disorder and its Association With Body Features in Female Medical Students

Abstract: BackgroundBody dysmorphic disorder (BDD) is a distressing psychiatric disorder. So far there have not been any studies on BDD in Saudi Arabia.ObjectivesThe aim of this study was to determine the prevalence of body dysmorphic disorder in female medical students and to investigate whether there is an association between BDD and body features of concern, social anxiety and symptoms of BDD.Materials and MethodsA cross sectional study was carried out on female medical students of the college of medicine, King Saud … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 17 publications
4
26
1
Order By: Relevance
“…In addition to obesity/overweight, concerns related to the skin and nose were the most frequently reported among female adolescents in the current study. Female medical students in Riyadh reported consistent findings, with the skin and fat accounting for 75% and 68.8% of bodily concern, respectively 28 . This was also relatively in agreement with the concerns of Pakistani medical students, where body weight, skin, and teeth represented the main concerns in the participants with BDD 26 .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In addition to obesity/overweight, concerns related to the skin and nose were the most frequently reported among female adolescents in the current study. Female medical students in Riyadh reported consistent findings, with the skin and fat accounting for 75% and 68.8% of bodily concern, respectively 28 . This was also relatively in agreement with the concerns of Pakistani medical students, where body weight, skin, and teeth represented the main concerns in the participants with BDD 26 .…”
Section: Discussionsupporting
confidence: 69%
“…On the national level, only one study has investigated the patterns of BDD among female medical students. Among 365 participants from King Saud University, Riyadh, Shaffi Ahamed et al 28 . found that 4.4% (CI: 2.54, 7.04) were BDD positive.…”
Section: Discussionmentioning
confidence: 99%
“…This study examined the prevalence of BDD in a large sample of university students and BDD’s association with a range of clinical measures and questionnaires focusing on impulsivity and compulsivity. We found that the point prevalence of BDD was 1.7%, a rate similarly observed in community samples (Enander et al, 2018; Rief et al, 2008), although slightly lower than some other studies (2.4%; Koran et al, 2009), and considerably lower than that found in a small study (n=133) of university students (5.3%) (Bohne et al, 2002; see also Shaffi Ahamed et al, 2016 in female medical students; [4.4%]). Prevalence findings for BDD would be expected to differ between studies, since studies – statistically speaking – constitute samples from underlying populations (and therefore have intrinsic variance); also this may reflect differences in the nature of the cohorts examined (e.g.…”
Section: Discussionsupporting
confidence: 40%
“…students (Grant, Lust, & Chamberlain, 2019;Singh & Veale, 2019). The prevalence of BDD in American and Turkish students were 4% and 4.8%, respectively (Ahamed, et al, 2016;Koran, Abujaoude, Large, & Serpe, 2008). Many studies have suggested that a higher rate of negative affect is associated with body image dissatisfaction (Annesi & Gorjala, 2010;Lattimore & Hutchinson, 2010) and body image distortion (Farrell, Lee, & Shafran, 2005;Taylor & Cooper, 1992).…”
Section: Introductionmentioning
confidence: 99%